A systematic review of high-frequency transcranial magnetic stimulation on motor cortex areas as a migraine preventive treatment. (28th November 2019) - Hulla, Ryan; Liegey-Dougall, Angela
Background: The results of high-frequency repetitive transcranial magnetic stimulation (rTMS) over the dorsolateral prefrontal cortex for migraine have been inconsistent. However, high-frequency rTMS over the motor cortex is a treatment that may be effective in relieving symptoms of migraine with a low risk of side effects. Methods: A systematic review of high-frequency rTMS over the brain motor cortex areas in human participants was conducted to assess efficacy in treating migraine. Articles that were not looking at migraine patients, stimulation over the left motor cortex, or were not in English were excluded. Nine articles representing eight experiments using high-frequency rTMS over the motor cortex areas for migraine in human participants were extracted from the databases of PubMed, PsycINFO, MedLine, CINAHL, and BioMed Central. Results: Two-hundred and seven of 213 patients completed treatment throughout all the studies examined. High-frequency rTMS over the motor cortex areas for migraine improved migraine frequency in seven of eight studies. Two of the eight studies were randomized controlled trials at low risk for biases and found high-frequency rTMS over the motor cortex areas effective in improving migraine frequency and severity. Other details of treatment prescription and symptoms were also examined. Conclusion: High-frequency rTMS over the motor cortex areas for migraine demonstrated efficacy as a migraine treatment, had minimal side effects, and should be further investigated.